2018
DOI: 10.3390/en11123434
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Heat-Conducting Solid Wall and Heat-Generating Element on Free Convection of Al2O3/H2O Nanofluid in a Cavity with Open Border

Abstract: Development of modern electronic devices demands a creation of effective cooling systems in the form of active or passive nature. More optimal technique for an origination of such cooling arrangement is a mathematical simulation taking into account the major physical processes which define the considered phenomena. Thermogravitational convection in a partially open alumina-water nanoliquid region under the impacts of constant heat generation element and heat-conducting solid wall is analyzed numerically. A sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Authors have shown that the effective heat removal from the heated element is for the centered element within a tilted domain of p /3 angle. The previous work has been extended by Sheremet et al (2018), they have examined the influence of thermally-conducting border and thermally-producing unit in a partially open cavity. It has been shown that when a heated element is located close to the cold surface, an influence of nano-sized alumina particles is more significant for weak convective motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have shown that the effective heat removal from the heated element is for the centered element within a tilted domain of p /3 angle. The previous work has been extended by Sheremet et al (2018), they have examined the influence of thermally-conducting border and thermally-producing unit in a partially open cavity. It has been shown that when a heated element is located close to the cold surface, an influence of nano-sized alumina particles is more significant for weak convective motion.…”
Section: Introductionmentioning
confidence: 99%
“…An employing of the metallic nano-sized particles of great heat conductivity allows to rise the effective heat conductivity of the considered nanosuspension. The natural convection of nanoliquids behavior in open chambers has been researched in Kefayati et al (2012b); Nasrin et al (2013); Mahmoudi et al (2011); Bondareva et al (2017); Kalidasan and Kanna (2017); Miroshnichenko et al (2018); Sheremet et al (2018); Mehrizi et al (2012); Kalidasan et al (2017); Al-Rashed et al (2019). Thus, Kefayati et al (2012b) have investigated thermal convection in an open nanoliquid domain of different aspect ratios using the lattice Boltzmann technique (LBM).…”
Section: Introductionmentioning
confidence: 99%
“…The cavities have been extensively studied in previous and recent studies owing to its important engineering applications. Different characteristics of convection heat transfer were studied to improve or control the heat transfer process in homogeneous cavities (Tahmasebi et al , 2018; Sheikholeslami et al , 2019; Mehryan et al , 2019), cavity with MHD effects (Sadiq et al , 2018; Alsabery et al , 2018b, Bondareva and Sheremet, 2018), conjugate heat transfer (Alsabery et al , 2018a, Alsabery et al , 2017), layered cavities (Ghalambaz et al , 2018; Mehryan et al , 2019b, Sheremet et al , 2018; Miroshnichenko et al , 2018), cavity with obstacles (Alsabery et al , 2019; Abouali and Falahatpisheh, 2009; Astanina et al , 2018; Bondarenko et al (2019), Alsabery et al , 2018d), in partitioned cavities such as a cavity partially filled with a layer of porous media (Chamkha and Ismael, 2014; Mehryan et al , 2019), diagonally divided square cavity (Varol et al , 2009), gas chamber divided by a permeable membrane (de Almeida and Hart, 2017), a cavity with an off-center partition (Tatsuo et al , 1987), a cavity with multiple vertical partitions (Nishimura et al , 1988), a vertically divided cavity (Oztop et al , 2009), divided cavities with various thermal boundary conditions (Oztop et al , 2009), a partitioned cavity subject to a uniform heat flux (Kahveci, 2007) and partitioned cavities with various thermal boundary conditions (Xu et al , 2009; Kalabin et al , 2005; Küttler and Wall, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the global heat transfer rate was enhanced with an increase in the Rayleigh number and of the emissivity of the surface for both the heat generating and the isothermal heat sources. Sheremet et al [13] investigated natural convection thermal transmission in a partially open alumina-water nanoliquid area under the effect of vertical solid mural and local heat-generating source. They concluded that the influence of nano-sized alumina particles was more significant in the case of low intensive liquid circulation and when the heat source was located near the cooling wall.…”
Section: Introductionmentioning
confidence: 99%